Study of changes in biochemical parameters of preeclampsia patients, a prospective five year study - Saha, Aditi; Gupta, Anirban Das (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Preeclampsia is associated with changes in biochemical parameters like hepatic dysfunction, increase in blood glucose, thrombocytopenia, urea, creatinine, uric acid, alteration in lipid profile, hypoalbuminemia, electrolyte and C-reactive protein. Based on variability in literature regarding biochemical parameters present study has been designed to evaluate the changes in biochemical parameters in preeclampsia patients in tertiary care hospital. Methods: Pregnant women with pre eclampsia attending OPD of obstetrics department were enrolled for this study based on following inclusion and exclusion criteria. Similarly normotensive pregnant women were enrolled as control per same inclusion and exclusion criteria. Results: Total platelet count was significantly lower in preeclampsia patients then control (2.02±0.7 lakh/µl versus 3.29±.58 lakh/µl). Blood urea was significantly higher in preeclampsia patients than control (29.22±4.56 mg/dl versus 18.32±6.23 mg/dl), (p=0.0001) serum uric acid was significantly higher in preeclampsia patients than control (9.22±1.11 mg/dl versus 5.89±.89 mg/dl). HOMA IR was significantly higher in preeclampsia patients then control (4.52±1.68 versus 2.23±1.98). Conclusions: From present study we can conclude preeclampsia patients were frequent in nulliparous. Preeclampsia is associated with thrombocytopenia. Except increase in AST other hepatic parameters were in normal range and comparable to control. FPG, FPI and HOMA IR were elevated in our finding and it indicates a state of insulin resistance. Preeclampsia patients were also having dyslipidemia. Serum uric acid creatinine and blood urea was significantly higher in preeclampsia patients.